A BAHD hydroxycinnamoyltransferase from Actaea racemosa catalyses the formation of fukinolic and cimicifugic acids - Werner, Victoria; Petersen, Maike (Planta, 2019)
Actaea racemosa (syn. Cimicifuga racemosa) is known to contain triterpene lactone glycosides and cimicifugic acids. The latter are esters of various hydroxycinnamic or benzoic acids with piscidic or fukiic acid. Amplification of a nucleotide sequence from A. racemosa, that was already known as HCT1 from an EST approach, and its expression in E. coli resulted in a protein that was able to catalyse the formation of several cimicifugic acids. For the characterisation of this hydroxycinnamoyltransferase (hydroxy)cinnamoyl-coenzyme A thioesters were synthesised as donor substrates and piscidic acid isolated as acceptor substrate. The lowest K m-value with 6.8 µM was determined for p-coumaroyl-CoA. More than 30 possible acceptor substrates were tested, but only piscidic acid and putatively fukiic acid were accepted. The apparent K m-value for piscidic acid was 32.3 µM. High expression of the hydroxycinnamoyltransferase gene was found in roots, but the content of cimicifugic acids was higher in leaves and flowers than in roots. This work describes for the first time a biosynthetic step in the formation of cimicifugic acids catalysed by a so far uncharacterised hydroxycinnamoyltransferase accepting piscidic acid as acceptor substrate thus being a hydroxycinnamoyl-CoA: piscidic acid hydroxycinnamoyltransferase (ArHPT1; cimicifugic acid synthase).